Pengaruh Perebusan Telur Ayam Kampung Terhadap Kadar Protein - Khaerati, Khildah (Media Eksakta, 2011)
The aim of this research was to compareÂ the protein content ofÂ â€œ kampungâ€ chickenâ€™s eggÂ before and after poaching. Qualitative analysis was done using Biuret, Millonâ€™s, and Ninhydrin reagents, producing violet, red, and blue-violet, respectively. Quantitative analysis was done by the Kjeldahl method. The resulf of the investigation showed that length of poaching time influenced the protein content of â€œkampung